2020
DOI: 10.1126/sciadv.abb1244
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A1–dependent tethering promotes extracellular vesicle aggregation revealed with single–extracellular vesicle analysis

Abstract: Extracellular vesicles (EVs) including plasma membrane–derived microvesicles and endosomal-derived exosomes aggregate by unknown mechanisms, forming microcalcifications that promote cardiovascular disease, the leading cause of death worldwide. Here, we show a framework for assessing cell-independent EV mechanisms in disease by suggesting that annexin A1 (ANXA1)–dependent tethering induces EV aggregation and microcalcification. We present single-EV microarray, a method to distinguish microvesicles from exosomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
96
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(104 citation statements)
references
References 43 publications
4
96
0
1
Order By: Relevance
“…However, we did visualize that EVs had an affinity for collagen fibrils and used these fibrils as scaffolding as the EVs aggregate and mineralize. We recently showed that calcifying EVs contain annexin A1, which functioned as a membrane-binding protein that mediated EV aggregation ( 28 ). Other annexins were also implicated in interactions with collagen in the extracellular matrix and have been hypothesized to mediate calcium influx into EVs ( 11 , 26 , 28 , 53 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we did visualize that EVs had an affinity for collagen fibrils and used these fibrils as scaffolding as the EVs aggregate and mineralize. We recently showed that calcifying EVs contain annexin A1, which functioned as a membrane-binding protein that mediated EV aggregation ( 28 ). Other annexins were also implicated in interactions with collagen in the extracellular matrix and have been hypothesized to mediate calcium influx into EVs ( 11 , 26 , 28 , 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages have also been shown to release procalcifying vesicles ( 20 , 21 ). Thus, just as bone formation is hypothesized to be an active, cell-driven process ( 22 , 23 ), mediated by calcifying matrix vesicles, atheroma-associated calcification may similarly be initiated by the production and aggregation of calcifying EVs ( 11 , 20 , 24 28 ).…”
mentioning
confidence: 99%
“…A recent study, using human cardiovascular cells, demonstrated that Annexin A1 induces EVs aggregation and microcalcification formation that promote CVD. These findings could lead to development of therapeutic strategies in CVD [ 120 ].…”
Section: Extracellular Vesicle As Biomarkers In Cvdmentioning
confidence: 99%
“…Some studies have highlighted the role of EVs derived from valvular interstitial cells (VICs) in VC [ 121 , 125 , 130 ]. Thus, Cui et al performed a proteomic analysis of EVs from calcified VICs and identified the up-regulation of calcification regulators, such as calcium-binding annexins [ 130 ].…”
Section: Extracellular Vesicles In a Pathological Setting: A Focusmentioning
confidence: 99%
“…Furthermore, Bouchareb et al found that mineralization of the aortic valve after mechanical strain was promoted by spheroid microvesicles derived from VICs [ 125 ]. Lastly, Rogers et al reported that annexin A1 tethering of VIC-derived EVs induced microcalcification and EV aggregation [ 121 ].…”
Section: Extracellular Vesicles In a Pathological Setting: A Focusmentioning
confidence: 99%